We love open source software. No, you can’t have our code - Askey, Dale (My University, 2008)
Librarians are among the strongest proponents of open source software. Paradoxically, libraries are also among the least likely to actively contribute their code to open source projects. This article identifies and discusses six main reasons this dichotomy exists and offers ways to get around them.
Keywords: Open source; Software; Libraries